Sociodemographic, behavioral, and environmental factors associated with the incidence of leptospirosis in highlands of Ponorogo Regency, Province of East Java, Indonesia - Hari Basuki Notobroto; Yudied Agung Mirasa; Firman Suryadi Rahman (Elsevier, 2021)
Leptospirosis is a zoonotic disease that globally spreads and has the potential to become an epidemic. In Indonesia, the incidence of leptospirosis tends to increase with case fatality rate ranged from 5 to 12%. Ponorogo is one regency in Province of East Java, Indonesia that has high incidence of leptospirosis. The objective of this study was to identify sociodemographic, behavioral, and environmental factors associated with incidence of leptospirosis in highlands of Ponorogo regency. The study used case control design conducted in 15 villages in the highlands of Ponorogo regency. The sample was composed of 28 cases of leptospirosis and 112 nonleptospirosis. The variables of this study were sociodemographic, behavioral factors, environmental factors, and incidence of leptospirosis. Data was collected by interview using questionnaire and observation of environmental conditions. Data was analyzed using chi square and logistic regression. The result showed that factors associated with the incidence of leptospirosis were education (p = 0.019), occupation (p = 0.003), health practice (p = 0.007), house density (p = 0.013), livestock ownership (p = 0.004), distance from house to cowshed (p = 0.024), cow ownership (p = 0.010), and the presence of rats in the house (p = 0.050). The result of logistic regression analysis showed that the variables dominantly associated with the incidence of leptospirosis were livestock ownership, education (low), house density (crowded), and distance from house to cowshed (less than 10 m). In conclusion, sociodemographic, behavioral, and environmental factors were associated with the incidence of leptospirosis in highlands of Ponorogo Regency.